2021
DOI: 10.1016/j.jad.2021.08.144
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and mental health during the COVID-19 pandemic: Findings from Minnesota and Hong Kong

Abstract: Background : Previous COVID-19 pandemic research has focused on assessing the severity of psychological responses to pandemic-related stressors. Little is understood about (a) resilience as a mental health protective factor during these stressors, and (b) whether families from Eastern and Western cultures cope differently. This study examines how individual resilience and family resilience (i.e., family resources and perception) moderate the associations between pandemic-related stressors and symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 30 publications
(44 reference statements)
4
44
0
1
Order By: Relevance
“…The results supported our third hypothesis that resilience would buffer the relationship between COVID-19 worries and MWB. This finding supports previous research indicating that resilience buffered the relationship between various negative pandemic related constructs and MWB (e.g., Killgore et al, 2020 ; Chan et al, 2021 ; Paredes et al, 2021 ; Shah et al, 2022 ). The implication is that for those with higher levels of resilience, the possible effects of COVID-19 worries are abated.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results supported our third hypothesis that resilience would buffer the relationship between COVID-19 worries and MWB. This finding supports previous research indicating that resilience buffered the relationship between various negative pandemic related constructs and MWB (e.g., Killgore et al, 2020 ; Chan et al, 2021 ; Paredes et al, 2021 ; Shah et al, 2022 ). The implication is that for those with higher levels of resilience, the possible effects of COVID-19 worries are abated.…”
Section: Discussionsupporting
confidence: 91%
“…A large-scale review of MWB during the pandemic also found that generally, more resilient individuals were faring more positively (Manchia et al, 2022 ). Importantly, resilience has substantially reduced or eliminated the effect of various COVID-19 concerns on MWB (Chan et al, 2021 ; Kavčič et al 2021; Kocjan et al, 2021 ; Paredes et al, 2021 ; Shah et al, 2022 ).…”
Section: Resilience and Well-beingmentioning
confidence: 99%
“…In particular, the dyadic association between stress and well‐being demonstrates the interdependence of experience and responses between parents and children during the pandemic (De Neve & Kawachi, 2017 ). As such, psychologists, therapists, and other mental health professionals should emphasize the family system as a unit of care and intervention (Chan et al, 2021 ). To facilitate psychological adjustment following the COVID‐19 outbreak, effective family‐based interventions are needed to address stress‐related symptoms and equip parents and children with effective coping strategies in the face of adversity.…”
Section: Discussionmentioning
confidence: 99%
“…In the COVID-19 pandemic, several studies have analyzed the effects of resilience on mental health. According to Chan et al [ 28 ], in both individualistic and collectivistic cultures, high levels of resilience buffer the association between traumatic events and the appearance of anxious and depressive symptomatology. Havnen et al [ 29 ] consider that such buffering effects would result from the application of a set of coping resources appropriate to the traumatic aspects of the pandemic.…”
Section: Introductionmentioning
confidence: 99%